THE ROLE OF BANKING AND FINANCIAL SYSTEM IN DEVELOPMENT OF TOURISM IN UZBEKISTAN - Musaev, Malikjon Karomatovich (Educational Research in Universal Sciences, 2023)
This article discusses recent development of tourism in Uzbekistan and the role of banking and financial institutions in the development of tourism. Moreover, possible challenges to the visitors to the country and their solutions as well as suggestions to flourish tourism industry are stated in the article.